ESTIMATION OF ECONOMIC LOSSES TO THE COMMUNITY AS A RESULT OF BATIK WASTE POLLUTION - Miadatul Abdiyah; Norita Vibriyanto (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to estimate the total economic losses caused by batik waste pollution and identify the factors that Influence it. This study uses a quantitative approach, combining cost of illness (COI) and replacement cost (RC) to estimate the value of economic losses, and multiple linear regression to identify factors that influence economic losses. Primary data were collected through interviews with 35 respondents within a 100-meter radius of the polluted river who had used river water. The results showed that the total economic loss reached IDR 1,539,255/month, with an average loss of IDR 114,807/household/month. The factors that had a significant positive effect on economic loss were length of stay and income. The longer the length of stay, the greater the economic loss, and the higher the income, the greater the economic loss. Meanwhile, the variables of family dependents and distance from home had a significant negative effect; the more family dependents, the greater the economic loss, and the farther the distance from home, the lower the economic loss. This study emphasises the importance of integrated batik waste management as the basis for formulating sustainable environmental policies.